2014
DOI: 10.1186/scrt446
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of efficacy and safety of Wharton’s jelly mesenchymal stem cell transplantation in patients with type 2 diabetes mellitus

Abstract: IntroductionStem cell therapy has recently been introduced to treat patients with type 2 diabetes mellitus (T2DM). However, no data are available on the efficacy and safety of allogeneic Wharton’s Jelly-derived mesenchymal stem cell (WJ-MSC) transplantation in patients with T2DM. Here we performed a non-placebo controlled prospective phase I/II study to determine efficacy and safety of WJ-MSC transplantation in T2DM.MethodsTwenty-two patients with T2DM were enrolled and received WJ-MSC transplantation through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
120
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 31 publications
10
120
0
Order By: Relevance
“…Therefore, we selected IL-6 to assess the function of MSCs after transplantation. In support of previous research [30], IL-6 levels increased with time, accompanied by CRP reductions. CRP is a nonspecific sensitive index reflecting the state of inflammation; its level is positively correlated with the development of DR [33].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, we selected IL-6 to assess the function of MSCs after transplantation. In support of previous research [30], IL-6 levels increased with time, accompanied by CRP reductions. CRP is a nonspecific sensitive index reflecting the state of inflammation; its level is positively correlated with the development of DR [33].…”
Section: Discussionsupporting
confidence: 68%
“…Most DR clinical trials conducted to date have focused on improving local circulation and metabolism, while ignoring the improvement in general condition [8,26,28]. Moreover, previous trials investigating MSC for patients with DR did not report retinal changes, although most showed an improvement in glucose metabolism [16,29,30]. Herein, we describe the outcomes of ABMSC transplantation in patients with DR, including changes in glucose metabolism, immune function, visual function, and retina microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous clinical trials, using Wharton's jelly derived MSCs, Liu et al (2014) showed that MSC transplantation significantly decreased the levels of glucose and glycated hemoglobin, while improving C-peptide levels and beta cell function (Liu et al, 2014). In another study, Jiang et al (2011) (Jiang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…After the transplantation, Tong et al showed that C-peptide levels increased in all of the patients; in fact reduced insulin dose corresponded with improved C-peptide levels (Tong et al, 2013). In 2014, 22 patients with T2D were treated with Wharton's jelly derived MSC (WJ-MSC) transplantation through intravenous injection and intra-pancreatic endovascular injection (Liu et al, 2014). Liu et al showed that WJ-MSC transplantation significantly decreased the levels of glucose, improved C-peptide levels, and improved beta cell function, all without any adverse effects (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation